Isotropic tough aluminum alloy and preparation method thereof
By optimizing the chemical composition and process parameters of aluminum alloy, the problem of insufficient tissue anisotropy and toughness performance in laser additive manufacturing is solved, and the isotropy and toughness performance of aluminum alloy is significantly improved.
Patent Information
- Application Number
- CN202411907599.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
In the laser additive manufacturing, existing aluminum alloys have problems such as severe tissue anisotropy and insufficient toughness performance.
By optimizing the weight percentage of the aluminum alloy, including Cu, Ni, Mn, Zr, Ti elements, and adjusting the laser additive manufacturing process parameters and subsequent heat treatment processes, the isotropic and toughness properties of the aluminum alloy are improved.
The structure uniformity and isotropy of aluminum alloy are improved. The microstructure is an isometric crystal structure, the grain size is suitable, the precipitation phase is uniformly distributed, and the toughness is manifested as tensile strength 240~340MPa and the elongation is ≥20%.
Smart Images

Figure CN119640111A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal additive manufacturing, and in particular, to obtaining an isotropic tough aluminum alloy through powder optimization design, additive manufacturing process regulation and subsequent heat treatment. Background Art
[0002] Aiming at the development demand of lightweight in aerospace, transportation, energy facilities and other fields, aluminum alloys with low density, high thermal conductivity and high specific strength have shown significant advantages. For aluminum alloy parts with complex shapes such as shell frames, radiators, brackets, etc. in the above application fields, traditional casting, extrusion, cutting and other production processes have shortcomings such as long production cycle and low processing accuracy. Laser additive manufacturing technology is based on the three-dimensional CAD model of the component. By laser melting metal powder layer by layer, it can realize the direct printing of complex parts. It has the advantages of fast processing efficiency, simple process, economic convenience and so on. At present, a lot of research work has been carried out on laser additive manufacturing of aluminum alloys. One of its important research contents is to further improve the mechanical properties such as strength and toughness of aluminum alloy components [non-patent literature: ZH Bai, F. Qiu, JX Xue, BQ Zhang, QC Jiang. Materials Characterization, 2015, 100, 36-40].
[0003] Existing research mainly improves the mechanical properties of printed structural parts by regulating the composition of aluminum alloys and laser additive manufacturing processes, and has achieved some remarkable results. In terms of composition regulation, by adding strengthening phase elements such as Ni, Mn, Fe, Cr, and Zr, aluminum alloys can obtain solid solution strengthening and precipitation strengthening, thereby improving the hardness and strength of the alloy. Xiao et al. successfully improved the defects such as pores and cracks during aluminum alloy printing by adding Nb elements to Al-Mg-Cu-Zn alloys, and obtained good mechanical properties of aluminum alloys with a tensile strength of 422 MPa and an elongation of 17.1% [Non-patent literature: F. Xiao, SBWang, YX Wang, D. Shu, GL Zhu, BD Sun, D. StJohn. Journal of Alloys and Compounds, 2022, 900, 163427]. On the other hand, by regulating the laser energy density, scanning strategy, and subsequent heat treatment process of laser additive manufacturing, an optimized process and processing window are obtained, thereby improving the mechanical properties of aluminum alloys. Sun et al. obtained a high-strength Al-Cu-Mg alloy with a tensile strength of 520.3 MPa and an elongation of 9% under optimized laser dose density and subsequent solution treatment conditions [non-patent literature: TT Sun, J. Chen, Y. Wu, ML Wang, YA Fu, HZ Wang, HW Wang. Materials Science&Engineering A, 2022, 850,143531]. The above research significantly increased the strength of aluminum alloys, but their elongation is usually less than 20%. In addition, aluminum alloys still have shortcomings such as severe anisotropy of the microstructure.
[0004] It can be seen from this that the composition and processing technology of aluminum alloys still need to be further optimized to obtain aluminum alloy structural parts with uniform structure, isotropy and good toughness. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an aluminum alloy with uniform structure, high isotropy and good toughness; by adjusting the weight percentage of elements in the aluminum alloy, laser additive manufacturing process parameters, and subsequent heat treatment process to improve the isotropy of the aluminum alloy and improve its toughness.
[0006] According to one aspect of the present invention, an isotropic toughness aluminum alloy optimized composition is provided:
[0007] Preferably, the isotropic ductile aluminum alloy comprises the following chemical components in weight percentage: Cu 3-6%, Ni 0.5-2%, Mn 0.1-0.5%, Zr 0.3-1.5%, Ti 0.1-0.2%, and the balance is Al. The isotropic ductile aluminum alloy is prepared using aluminum alloy powder as raw material through a laser additive manufacturing process.
[0008] Further preferably, the isotropic ductile aluminum alloy comprises the following chemical components in weight percentage: Cu 4-5%, Ni 1-1.5%, Mn 0.2-0.4%, Zr 0.5-1.2%, Ti 0.12-0.18%, and the balance is Al.
[0009] As one of the best preferred solutions, the isotropic ductile aluminum alloy includes the following chemical components in weight percentage: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al.
[0010] In the present invention, the content of Cu, Ni, Mn, Zr and Ti elements is controlled to adjust the uniformity of the structure and the strength and toughness of the aluminum alloy. Based on the limiting solid solubility of the Cu, Ni, Mn, Zr and Ti elements in the aluminum matrix, if the element content is too high, the aluminum alloy will be segregated, the precipitation phase structure will be uneven, and the toughness of the aluminum alloy will be reduced; if the element content is too low, the solid solution effect will be poor, and there will be no precipitation phase strengthening effect, resulting in reduced strength of the aluminum alloy.
[0011] According to another aspect of the present invention, a method for preparing an isotropic toughness aluminum alloy is provided:
[0012] Preferably, the method for preparing the isotropic ductile aluminum alloy comprises the following steps:
[0013] Step 1: prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage, and obtain aluminum alloy powder with particle size D10=18±7.0 μm, D50=34±7.0 μm, D90=58±15.0 μm, D100=89±15.0 μm by sieving, and the powder particle size relationship D50 / (D100-D10) satisfies the range of 30-65%;
[0014] Step 2: vacuum drying the aluminum alloy powder prepared in step 1 at 80-140°C for 5-10 h, and pre-preparing an aluminum alloy powder bed with a thickness of 20-50 μm on the surface of the substrate preheated at 120-240°C by a scraper;
[0015] Step 3: Print aluminum alloy using laser additive manufacturing equipment, with a laser power range of 300-400 W, a scanning speed range of 350-500 mm / s, a scanning interval range of 60-150 μm, a scanning deflection angle of 0-90°, and a protective atmosphere of any one of argon, helium, and argon / hydrogen mixed gas, with an oxygen content of ≤100 ppm;
[0016] Step 4: Use a muffle furnace to heat treat the printed aluminum alloy at different temperatures and times. The heating temperature range is 450-540 °C, the holding time is 0.5-3 h, the heat treatment atmosphere is any one of argon, helium, and argon / hydrogen mixed gas, and the cooling method after heat treatment is water cooling or oil cooling.
[0017] Further preferably, in step 1, the spherical aluminum alloy powder is prepared by a vacuum air atomization method, and the particle size range after screening is D10=18±5.0 μm, D50=34±5.0 μm, D90=58±10.0 μm, D100=89±10.0 μm, and the powder particle size relationship D50 / (D100-D10) satisfies the range of 34-59%.
[0018] As one of the best preferred solutions, in step 1, the powder particle size range of the spherical aluminum alloy includes D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) is 48%.
[0019] In the present invention, in step 1, D50 / (D100-D10) is controlled to improve the forming quality of laser additive manufacturing of aluminum alloy. When D50 / (D100-D10) is too small, a large amount of fine powder or oversized coarse powder exists in the powder, the powder fluidity decreases, and it is not conducive to the pre-setting of the powder bed; when D50 / (D100-D10) is too large, the gap between the powders is large, and hole defects are prone to appear after additive manufacturing. In addition, when D50 / (D100-D10) is too small or too large, it is easy to cause uneven distribution of elements during laser rapid melting-solidification, thereby reducing the degree of isotropy of the aluminum alloy and increasing the difficulty of regulating strength and toughness.
[0020] Further preferably, in step 2, the aluminum alloy powder is vacuum dried at 100-120°C for 7-8 h, and a powder bed with a thickness of 25-45 μm is pre-deposited on the surface of the substrate at a preheating temperature of 140-180°C by a scraper.
[0021] Further preferably, in step 3, the laser power range is 320-360 W, the scanning speed range is 400-500 mm / s, the scanning interval range is 70-120 μm, the scanning deflection angle is 30-90°, the protective atmosphere is any one of argon, helium, and argon / hydrogen mixed gas, and the oxygen content is ≤100 ppm.
[0022] As one of the best preferred solutions, the laser power is 340 W, the scanning speed is 450 mm / s, the scanning interval range is 90 μm, the scanning deflection angle is 67°, the protective atmosphere is argon, and the ambient oxygen content is 100 ppm.
[0023] In the present invention, when the laser power is too low, the scanning speed is too high, and the scanning interval is too large, hole formation defects are likely to occur in the aluminum alloy; when the laser power is too high, the scanning speed is too low, and the scanning interval is too small, thermal cracks and tissue coarsening are likely to occur in the aluminum alloy, thereby reducing the anisotropy and toughness of the tissue. When the scanning deflection angle is too small or too large, the preferred orientation of the tissue in the vertical direction is serious, resulting in a decrease in the degree of isotropy.
[0024] When used industrially, after completing step 3, it is separated from the substrate by wire cutting.
[0025] Further preferably, in step 4, the heat treatment temperature range is 490-530° C., the holding time is 0.5-2 h, the heat treatment atmosphere is any one of argon, helium, and argon / hydrogen mixed gas, and the cooling method after heat treatment is water cooling or oil cooling.
[0026] More preferably, in step 4, the heat treatment temperature range is 505-515° C., and the insulation time is 1-1.5 h.
[0027] In the present invention, when the heat treatment temperature is too high and the holding time is too long, the grain structure in the aluminum alloy is severely coarsened and the precipitation phase segregation phenomenon is serious; when the heat treatment temperature is too low and the holding time is too short, the recrystallization effect of the aluminum alloy is weak and the isotropy degree is low.
[0028] The present invention provides an aluminum alloy manufactured using the method according to any one of the above technical solutions, wherein the aluminum alloy microstructure is an equiaxed crystal structure, the grain size range is 1-25 μm, the recrystallized grains account for ≥50%, and the precipitated phase size range is 200 nm-1 μm.
[0029] After the printed part of the present invention is heat treated, the hardness difference between the XY plane and the XZ plane is ≤2 HV.
[0030] After heat treatment, the printed parts have a tensile strength of 240~340MPa and an elongation of ≥20%.
[0031] In the optimized solution, after heat treatment, the printed parts have a tensile strength of 290~340MPa and an elongation of 20~26%.
[0032] Through the above technical solutions, the present invention can achieve the following technical effects.
[0033] 1) Aluminum alloys can obtain fine and uniform microstructures, the isotropy of aluminum matrix grains is high, and the EBSD grain orientation pole figure density is ≤3;
[0034] 2) The precipitated phase in the aluminum alloy is submicron in size and is uniformly and dispersedly distributed;
[0035] 3) The elongation of aluminum alloy is ≥20%, showing good toughness performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a morphology diagram of the spherical aluminum alloy powder used in Example 1;
[0037] Figure 2 is a particle size distribution diagram of the spherical aluminum alloy powder used in Example 1;
[0038] Figure 3 The microstructure images and EBSD grain orientation diagram of the aluminum alloy after laser additive manufacturing and heat treatment obtained in Example 1 in the XY plane and XZ plane;
[0039] Figure 4 This is a grain type distribution diagram of the aluminum alloy after laser additive manufacturing and heat treatment in the XZ plane obtained in Example 1;
[0040] Figure 5 EBSD orientation pole figure of the aluminum alloy after laser additive manufacturing and heat treatment in the XZ plane direction obtained in Example 1;
[0041] Figure 6 The hardness histograms of the products obtained in Examples 1-4 and Comparative Examples 1-3 in the XY plane and XZ plane directions;
[0042] Figure 7 It is the tensile curve diagram of the products obtained in Examples 1-4 and Comparative Examples 1-3;
[0043] from Figure 1 It can be seen that the aluminum alloy powder has good sphericity and good fluidity, which is suitable for pre-setting the powder bed in the laser additive manufacturing step.
[0044] from Figure 2It can be seen that the D10 of the spherical aluminum alloy powder is 18.4 μm, D50 is 34.1 μm, D90 is 57.8 μm, D100 is 89.1 μm, and D50 / (D100-D10) is 48%. The powder particle size distribution is suitable for laser additive manufacturing of low-defect, isotropic aluminum alloys.
[0045] from Figure 3 It can be seen that the microstructure of the aluminum alloy after laser additive manufacturing and heat treatment includes equiaxed grains with a grain size of about 15 μm and precipitates with a size range of 500-1 μm and uniformly dispersed distribution.
[0046] from Figure 4 It can be seen that the grain type of aluminum alloy after laser additive manufacturing-heat treatment is mainly blue recrystallized grains, which account for about 80%.
[0047] from Figure 5 It can be seen that there is no obvious texture phenomenon in the aluminum alloy after laser additive manufacturing and heat treatment, the grain orientation is random, and the EBSD pole figure density is 2.12.
[0048] from Figure 6 It can be seen that under the optimal aluminum alloy composition, laser additive manufacturing process parameters and heat treatment process parameters, the hardness of the aluminum alloy in the XY plane and XZ plane directions is approximately the same.
[0049] from Figure 7 It can be seen that under the optimal aluminum alloy composition, laser additive manufacturing process parameters and heat treatment process parameters, the elongation of the aluminum alloy is ≥20%. DETAILED DESCRIPTION
[0050] The present invention is further described in detail with reference to the following examples, but is not limited to the following examples.
[0051] Example 1
[0052] A method for preparing an isotropic tough aluminum alloy, wherein the weight percentages of the elements in the aluminum alloy are: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al. The aluminum alloy preparation process is as follows:
[0053] Step 1: Prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage ( Figure 1 ), and sieved to obtain aluminum alloy powder with particle size D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, D50 / (D100-D10) is 48% ( Figure 2 );
[0054] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0055] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 340 W, a scanning speed of 450 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0056] Step 4: Heat treat the printed aluminum alloy at 510 °C for 1 h in a muffle furnace and then cool it with water.
[0057] Laser additive manufacturing-microstructure of aluminum alloy after heat treatment Figure 3 As mentioned above, both the XY plane and the XZ plane are composed of equiaxed grains with an average size of about 15 μm and dispersed precipitates with a size range of 0.5-1 μm. The recrystallized grains account for about 80% on the XZ plane ( Figure 4 ), and the orientation pole figure density of aluminum grains is only 2.12 ( Figure 5 ).like Figure 6 As shown in Figure 2, the hardness of aluminum alloy in the XY plane and XZ plane is approximately the same, about 95 HV and 94 HV respectively; Figure 7 As shown, the ultimate tensile strength in the tensile test is 339.2 MPa and the elongation is 20.2%.
[0058] Example 2
[0059] The difference between this embodiment and embodiment 1 is that the heat treatment holding time in step 4 is increased, and the other steps and parameters are the same; the weight percentage of each element in the aluminum alloy is: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al. The aluminum alloy preparation process is as follows:
[0060] Step 1: Prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage ( Figure 1 ), and screened to obtain particle sizes of D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) of 48% ( Figure 2 );
[0061] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0062] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 340 W, a scanning speed of 450 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0063] Step 4: Heat treat the printed aluminum alloy at 510 °C for 1.5 h in a muffle furnace and then cool it with water.
[0064] like Figure 6 As shown in Figure 2, the hardness of aluminum alloy in the XY plane and XZ plane is approximately the same, about 92 HV and 91 HV respectively; Figure 7 As shown, when the heat treatment time increases, the ultimate tensile strength of the aluminum alloy in the tensile test is 322.9 MPa and the elongation is 25.4%.
[0065] Example 3
[0066] The difference between this embodiment and embodiment 2 is that the heat treatment holding time in step 4 is further increased, and the other steps and parameters are the same; the weight percentage of each element in the aluminum alloy is: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti0.15%, and the balance is Al. The aluminum alloy preparation process is as follows:
[0067] Step 1: prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage, and perform sieving to obtain particle sizes of D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) of 48%;
[0068] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0069] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 340 W, a scanning speed of 450 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0070] Step 4: Heat treat the printed aluminum alloy at 510 °C for 2 h in a muffle furnace and then cool it with water.
[0071] like Figure 6 As shown in Figure 2, the hardness of aluminum alloy in the XY plane and XZ plane is approximately the same, about 90 HV and 91 HV respectively; Figure 7As shown in Figure 2, when the heat treatment time is further increased, the ultimate tensile strength of the aluminum alloy in the tensile test is 242.6 MPa and the elongation is 20.5%.
[0072] Example 4
[0073] The difference between this embodiment and embodiment 1 is that the heat treatment temperature in step 4 is increased, and the other steps and parameters are the same; the weight percentage of each element in the aluminum alloy is: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al. The aluminum alloy preparation process is as follows:
[0074] Step 1: prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage, and perform sieving to obtain particle sizes of D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) of 48%;
[0075] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0076] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 340 W, a scanning speed of 450 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0077] Step 4: Heat treat the printed aluminum alloy at 540 °C for 1 h in a muffle furnace and then cool it with water.
[0078] like Figure 6 As shown in Figure 2, the hardness of aluminum alloy in the XY plane and XZ plane is approximately the same, about 85 HV and 86 HV respectively; Figure 7 As shown, when the heat treatment temperature increases, the ultimate tensile strength of the aluminum alloy in the tensile test is 304.2 MPa and the elongation is 23.7%.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that step 4 is omitted, and other steps and parameters are the same: the weight percentage of each element in the aluminum alloy is: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al.
[0081] Step 1: prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage, and perform sieving to obtain particle sizes of D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) of 48%;
[0082] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0083] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 340 W, a scanning speed of 450 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0084] like Figure 6 As shown in Figure 2, the hardness of the unheat-treated aluminum alloy in the XY plane and the XZ plane is significantly different, which is about 109 HV and 98 HV respectively; Figure 7 As shown, the ultimate tensile strength of the aluminum alloy in the tensile test is 331.1 MPa and the elongation is 9.2%.
[0085] Comparative Example 2
[0086] The difference between this comparative example and comparative example 1 is that the laser scanning speed in step 3 is different, and the other steps and parameters are the same: the weight percentage of each element in the aluminum alloy is: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al.
[0087] Step 1: prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage, and perform sieving to obtain particle sizes of D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) of 48%;
[0088] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0089] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 340 W, a scanning speed of 300 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0090] like Figure 6 As shown in Figure 2, the hardness of the aluminum alloy without heat treatment and with reduced laser scanning speed in the XY plane and XZ plane is significantly different, which is about 112 HV and 95 HV respectively; Figure 7 As shown, the ultimate tensile strength of the aluminum alloy in the tensile test is 286.0 MPa and the elongation is 8.0%.
[0091] Comparative Example 3
[0092] The difference between this comparative example and comparative example 1 is that the laser power in step 3 is different, and the other steps and parameters are the same: the weight percentage of each element in the aluminum alloy is: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al.
[0093] Step 1: prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage, and perform sieving to obtain particle sizes of D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) of 48%;
[0094] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0095] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 280 W, a scanning speed of 450 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0096] like Figure 6 As shown in Figure 2, the hardness of the aluminum alloy without heat treatment and with reduced laser scanning speed in the XY plane and XZ plane is significantly different, which is about 105 HV and 103 HV respectively; Figure 7 As shown, the ultimate tensile strength of the aluminum alloy in the tensile test is 246.7 MPa and the elongation is 2.7%.
[0097] Comparative Example 4
[0098] The difference between this comparative example and comparative example 1 is that the Ni content in the aluminum alloy is different, and the other steps and parameters are the same: the weight percentage of each element in the aluminum alloy is: Cu 4.5%, Ni 2.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al.
[0099] Step 1: prepare spherical aluminum alloy powder according to the above chemical composition and element weight percentage, and perform sieving to obtain particle sizes of D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) of 48%;
[0100] Step 2: After the aluminum alloy powder prepared in step 1 is vacuum dried at 110 °C for 8 h, it is pre-placed on the surface of the preheated substrate through a scraper, the powder thickness is 30 μm, and the preheating temperature is 160 °C;
[0101] Step 3: Use laser additive manufacturing equipment to print aluminum alloy, with a laser power of 340 W, a scanning speed of 450 mm / s, a scanning pitch of 90 μm, a deflection angle of 67°, an argon protective atmosphere, and an ambient oxygen content of 100 ppm; then separate it from the substrate by wire cutting;
[0102] like Figure 6 As shown in Figure 2, the hardness of the unheat-treated aluminum alloy with a Ni content of 2.5 wt.% in the XY plane and the XZ plane is significantly different, which is about 111 HV and 102 HV respectively; Figure 7 As shown, the ultimate tensile strength of the aluminum alloy in the tensile test is 225.5 MPa and the elongation is 3.2%.
[0103] It can be seen from Example 1 and Comparative Example 1 that heat treatment is beneficial to reducing grain defects, promoting recrystallization process, improving organizational anisotropy, reducing the hardness difference of aluminum alloy in the XY and XZ plane directions, and is beneficial to improving the toughness properties of aluminum alloy.
[0104] Through Example 1, Example 2, Example 3 and Example 4, laser additively manufactured aluminum alloys all obtained good isotropy after heat treatment, and the hardness in the XY and XZ plane directions remained approximately the same; the tensile properties can be regulated by the temperature and time of the heat treatment. When the holding time remains unchanged, appropriately increasing the temperature can increase the degree of recrystallization, which is beneficial to increase the elongation; when the temperature remains unchanged, appropriately increasing the holding time is beneficial to increase the elongation. Excessively high heating temperature and excessively long holding time can easily lead to coarsening of the structure, at which time both the toughness performance and the tensile strength are significantly reduced.
[0105] It can be seen from Comparative Examples 1, 2 and 3 that the process parameters of laser additive manufacturing are one of the important factors affecting the isotropy and toughness of aluminum alloys. When the laser power is constant, a scanning speed that is too low will lead to coarsening of the aluminum alloy structure and serious element segregation; when the laser scanning speed is constant, a laser power that is too low will easily cause a large number of defects in the alloy. On the one hand, it will increase the hardness difference of the aluminum alloy in the XY and XZ directions, and on the other hand, it will seriously deteriorate the tensile strength and elongation.
[0106] It can be seen from Comparative Examples 1 and 4 that the element ratio in the aluminum alloy is another important factor affecting the toughness of the aluminum alloy. Too high a Ni content can easily lead to an increase in defects such as holes in the laser additively manufactured aluminum alloy, severe element segregation, and the formation of a large number of brittle intermetallic compounds, thereby reducing the tensile strength and toughness.
Claims
1. An isotropic tough aluminum alloy, characterized in that: The isotropic ductile aluminum alloy is prepared by a laser additive manufacturing process using aluminum alloy powder as a raw material. The isotropic ductile aluminum alloy includes the following chemical components in weight percentage: Cu 3-6%, Ni 0.5-2%, Mn 0.1-0.5%, Zr 0.3-1.5%, Ti 0.1-0.2%, and the balance is Al.
2. The isotropic tough aluminum alloy according to claim 1, characterized in that: The isotropic ductile aluminum alloy comprises the following chemical components in weight percentage: Cu 4-5%, Ni 1-1.5%, Mn 0.2-0.4%, Zr 0.5-1.2%, Ti0.12-0.18%, and the balance is Al.
3. The isotropic ductile aluminum alloy according to claim 1, characterized in that: The isotropic ductile aluminum alloy has the following chemical compositions in weight percentage: Composition: Cu 4.5%, Ni 1.5%, Mn 0.3%, Zr 1.0%, Ti 0.15%, and the balance is Al.
4. A method for preparing an isotropic tough aluminum alloy as claimed in any one of claims 1 to 3, characterized in that: The steps include: Step 1: Prepare spherical aluminum alloy powder according to the designed chemical composition and element weight percentage, and obtain aluminum alloy powder with particle sizes of D10=18±7.0 μm, D50=34±7.0 μm, D90=58±15.0 μm, and D100=89±15.0 μm through screening treatment, and the powder particle size relationship D50 / (D100-D10) meets the range of 30-65%; Step 2: vacuum drying the aluminum alloy powder prepared in step 1 at 80-140°C for 5-10 h, and pre-preparing an aluminum alloy powder bed with a thickness of 20-50 μm on the surface of the substrate preheated at 120-240°C by a scraper; Step 3: Print the aluminum alloy using laser additive manufacturing equipment, with a laser power range of 300-400 W, a scanning speed range of 350-500 mm / s, a scanning interval range of 60-150 μm, a scanning deflection angle of 0-90°, and a protective atmosphere of any one of argon, helium, and argon / hydrogen mixed gas, with an oxygen content of ≤100 ppm; then separate it from the substrate by wire cutting; Step 4: Use a muffle furnace to heat treat the printed aluminum alloy at different temperatures and times. The heating temperature range is 450-540 °C, the holding time is 0.5-3 h, the heat treatment atmosphere is any one of argon, helium, and argon / hydrogen mixed gas, and the cooling method after heat treatment is water cooling or oil cooling.
5. The method for preparing an isotropic tough aluminum alloy according to claim 4, characterized in that: In the step 1, the spherical aluminum alloy powder is prepared by a vacuum gas atomization method, and the particle size range after screening is D10=18±5.0 μm, D50=34±5.0 μm, D90=58±10.0 μm, D100=89±10.0 μm, and the powder particle size relationship D50 / (D100-D10) satisfies the range of 34-59%.
6. The method for preparing an isotropic tough aluminum alloy according to claim 5, characterized in that: The powder particle sizes of the spherical aluminum alloy include D10=18.4 μm, D50=34.1 μm, D90=57.8 μm, D100=89.1 μm, and D50 / (D100-D10) is 48%.
7. The method for preparing an isotropic tough aluminum alloy according to claim 4, characterized in that: The spherical aluminum alloy powder in step 2 is vacuum dried at 100-120°C for 7-8 hours, and an aluminum alloy powder bed with a thickness of 25-45 μm is pre-placed on the surface of the substrate with a preheating temperature of 140-180°C by a scraper.
8. The method for preparing an isotropic tough aluminum alloy according to claim 4, characterized in that: In step 3, the laser power range is 320-360 W, the scanning speed range is 400-500 mm / s, the scanning interval range is 70-120 μm, the scanning deflection angle is 30-90°, the protective atmosphere is any one of argon, helium, and argon / hydrogen mixed gas, and the oxygen content is ≤100 ppm.
9. The method for preparing an isotropic tough aluminum alloy according to claim 4, characterized in that: In step 4, the heat treatment temperature range is 490-530° C., the holding time is 0.5-2 h, the heat treatment atmosphere is any one of argon, helium, and argon / hydrogen mixed gas, and the cooling method after heat treatment is water cooling or oil cooling.
10. The method for preparing an isotropic tough aluminum alloy according to claim 4, characterized in that: The obtained aluminum alloy microstructure is an equiaxed crystal structure with a grain size range of 5-25 μm, a recrystallized grain ratio of ≥50%, and a precipitate phase size range of 200 nm-1 μm.